Two quaestiones on the eternity of the world by Guido Terreni - Giletti, A (Brepols Publishers, 2015)
The two quaestiones below address the problem of Aristotle’s theory of the eternity of the world and the theory of creatio ab aeterno. They were written by Guido Terreni, probably during the teens of the fourteenth century. Their dating and attribution are discussed in a companion article in this volume, which also examines the philosophical positions taken, their context in the Univesity of Paris, and their implications in how we view Terreni as a prominent inquisitor and proliﬁc writer against heresy.